2016
DOI: 10.1021/acscatal.6b02310
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Mechanics/Molecular Mechanics Insights into the Enantioselectivity of the O-Acetylation of (R,S)-Propranolol Catalyzed by Candida antarctica Lipase B

Abstract: Classical molecular dynamics (MD) simulations and combined quantum mechanics/molecular mechanics (QM/MM) calculations were used to investigate the origin of the enantioselectivity of the Candida antarctica lipase B (CalB) catalyzed O-acetylation of (R,S)-propranolol. The reaction is a two-step process. The initial step is the formation of a reactive acyl enzyme (AcCalB) via a tetrahedral intermediate (TI-1). The stereoselectivity originates from the second step, when AcCalB reacts with the racemic substrate vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 101 publications
(161 reference statements)
1
40
0
Order By: Relevance
“…The simulation system consisted of 23,641 atoms (TXS: 6133; cation: 53; PPi: 9; Mg 2+ : 3; Na + : 10; water: 17,433). The chosen MD setup is analogous to that of previous studies reported in the literature …”
Section: Methods and Computational Detailsmentioning
confidence: 99%
See 4 more Smart Citations
“…The simulation system consisted of 23,641 atoms (TXS: 6133; cation: 53; PPi: 9; Mg 2+ : 3; Na + : 10; water: 17,433). The chosen MD setup is analogous to that of previous studies reported in the literature …”
Section: Methods and Computational Detailsmentioning
confidence: 99%
“…Three MD simulations with different initial velocity distributions (referred to as MD1, MD2, and MD3) were performed for each complex to enhance sampling . All MD simulations were done with the CHARMM software package (version 35b2) .…”
Section: Methods and Computational Detailsmentioning
confidence: 99%
See 3 more Smart Citations